Disparities in multi-modal spatial access to primary and specialty care in U.S. neighborhoods: A cross-sectional and temporal analysis of health services - R. Blake Buchalter; Paul R. Gunsalus; Madeleine M. Blazel; Michael W. Kenyhercz; Jarrod E. Dalton (PLoS ONE, 2025)
Spatial access to care describes the ability of populations to travel to healthcare providers. Existing spatial access to care studies frequently utilize metrics constructed using car-specific travel to providers, potentially underestimating access in populations using other travel modalities (i.e., walking/transit). We present a novel multi-travel modality spatial access to care composite measure, a corresponding temporally representative open-source data resource, and a stratified analysis of neighborhood rural/urban and socioeconomic disparities. We utilized quarterly 2016–2020 Centers for Medicare and Medicaid Services Doctors and Clinicians National Downloadable Files to compute temporally representative multi-modal spatial accessibility to 56 healthcare provider classifications in U.S. census tracts and block groups. We performed tract-level analyses stratified by 2010 Rural-Urban Commuting Area Codes and 2016 Area Deprivation Index for a subset of provider types. We found that 1) non-metropolitan areas have poorer multi-modal spatial access to primary (P < 0.001), specialty (P < 0.001), pulmonology (P < 0.001), nephrology (P < 0.001), and cancer care (P < 0.001) than metropolitan areas both cross-sectionally and over time and 2) multi-modal primary care access was substantially poorer than multi-modal specialty care access in 2016 and this trend did not improve over time. We also produced a data resource for many provider types and an interactive spatial access map for a subset of provider classifications. After stratifying, we found significant disparities in spatial access to primary care, specialty care, pulmonology, nephrology, and cancer care in non-metropolitan areas. Our multi-modal spatial access measure and corresponding data resource may be useful for population health and clinical studies, public health entities, community stakeholders, health systems, and policymakers.